2020
DOI: 10.1002/smll.202005564
|View full text |Cite
|
Sign up to set email alerts
|

pH‐Dependent Morphology Control of Cellulose Nanofiber/Graphene Oxide Cryogels

Abstract: The precise control of the ice crystal growth during a freezing process is of essential importance for achieving porous cryogels with desired architectures. The present work reports a systematic study on the achievement of multi‐structural cryogels from a binary dispersion containing 50 wt% 2,2,6,6‐tetramethylpiperidin‐1‐oxyl, radical‐mediated oxidized cellulose nanofibers (TOCNs), and 50 wt% graphene oxide (GO) via the unidirectional freeze‐drying (UDF) approach. It is found that the increase in the sol's pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 57 publications
0
17
2
Order By: Relevance
“…Without the covalent reactions, the CNCCNT/GnP interactions are limited to physical interactions. [52,53] The Gibbs energy difference (ΔΔG b ), calculated by DFT analysis, for pCNT-pCNT, pGnPpGnP, and CNCCNT/GnP shows that the agglomeration remains highly probable if the CNC molecules, are attached by side-to-side physical (e.g., van der Waals) interactions, (Table 1; Figure S2, Supporting Information). CNC particles were modeled with glucan chains, labeled CNC nano particles, with similar interacting properties (see the Experimental Section and the Supporting Information for more details).…”
Section: Resultsmentioning
confidence: 99%
“…Without the covalent reactions, the CNCCNT/GnP interactions are limited to physical interactions. [52,53] The Gibbs energy difference (ΔΔG b ), calculated by DFT analysis, for pCNT-pCNT, pGnPpGnP, and CNCCNT/GnP shows that the agglomeration remains highly probable if the CNC molecules, are attached by side-to-side physical (e.g., van der Waals) interactions, (Table 1; Figure S2, Supporting Information). CNC particles were modeled with glucan chains, labeled CNC nano particles, with similar interacting properties (see the Experimental Section and the Supporting Information for more details).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Karageorgiou and Kaplan reported that the optimal pore size to promote osteogenesis was [300 µm [119], while the optimal pore diameter for neuronal cells has often been reported to be \100 µm [120][121][122]. However, strategies to control pore size and morphology in nanocellulosic cryogels are known, including regulation of the gel composition [123][124][125]; freeze-casting temperature and/or rate [123,126]; sol pH [127]; and nanocellulose morphology [126]. Furthermore, Tetik et al [128] have recently incorporated directional freezing with 3D printing, which enabled the production of controlled 3D geometries with aligned micropores.…”
Section: Marcus Johns and Emily Cranston (University Of British Colum...mentioning
confidence: 99%
“…Nevertheless, sponges made using dispersions at low pH are known to possess higher storage modulus. 93 Relative humidity is found to affect the compression load afforded by freeze-dried sponges; the higher the relative humidity, the weaker the sponge would be, so it can withstand a smaller load and for a shorter period of time. 94 Furthermore, it is reported that GO loses some of its oxygencontaining moieties during the freeze-drying process (increasing the C : O and I D : I G ratios from $1.6 to $2.1 and 0.84 to 0.99, respectively).…”
Section: Ice-templatingmentioning
confidence: 99%
“…5f , different regions of the aerogel possess varied spacing between the GO nanosheets and thus, pore density differs locally within the sample. In addition to rate and direction of freezing, the properties of these sponges are also governed by GO nanosheets' size, 92 pH, 93 and humidity. 94 Ultra-large GO nanosheets are reported to yield a better alignment with ultralow percolation threshold, which when reduced, would make better electrical conductors.…”
Section: Template-directed Formation Of Graphene-based Porous Materialsmentioning
confidence: 99%